2014
DOI: 10.1021/om5003599
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Delocalized κ2C,N-NHC-Amine Complexes of Rhodium, Iridium, and Ruthenium

Abstract: The development of a novel set of complexes bearing an NHC-amine ligand (C NHC -NH 2 ) is described. M(cod) complexes (M = Ir, Rh) and a Ru complex have been synthesized in which three different coordination modes of the ligand were established: monodentate, neutral bidentate, and anionic bidentate. The anionic bidentate coordination mode of the anionic C NHC -NH − ligand arises from deprotonation of the amine moiety of the neutral C NHC -NH 2 ligand. Ligand deprotonation proved to be reversible for the Rh and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Surprised by the solution behavior of L1 ·[Rh­(COD)­Cl], we searched for NMR data of similar rhodium-NHC complexes containing cyclooctadiene groups. On the basis of several literature reports, we found that these asymmetrical 1 H NMR patterns are characteristic for neutral square planar NHC rhodium­(I) complexes where the cyclooctadiene ligand occupies two coordination sites and the carbene and chlorine centers complete the metal coordination sphere. It was interesting finding that even amino- and quinoline-functionalized NHCs containing Rh­(COD)Cl fragments do not display coordination of the hemilabile moiety to the metal center as the etha four coordination of the COD ligand is preferred.…”
Section: Resultsmentioning
confidence: 65%
“…Surprised by the solution behavior of L1 ·[Rh­(COD)­Cl], we searched for NMR data of similar rhodium-NHC complexes containing cyclooctadiene groups. On the basis of several literature reports, we found that these asymmetrical 1 H NMR patterns are characteristic for neutral square planar NHC rhodium­(I) complexes where the cyclooctadiene ligand occupies two coordination sites and the carbene and chlorine centers complete the metal coordination sphere. It was interesting finding that even amino- and quinoline-functionalized NHCs containing Rh­(COD)Cl fragments do not display coordination of the hemilabile moiety to the metal center as the etha four coordination of the COD ligand is preferred.…”
Section: Resultsmentioning
confidence: 65%
“…All the other structural parameters are in good agreement with those observed for other similar complexes. [32][33][34][35] The steric bulk, measured as the percentage of buried volume (%V Bur ) of the N-cyclohexyl/N-o-isopropylphenyl NHC ligands with syn or anti phenyl groups on the backbone, was extracted using the SambVca program developed by Cavallo, 36 Scheme 4 Synthesis of Rh complexes 39-42. using the crystal data of the corresponding Rh complexes 39 and 40. The %V Bur values are 29.7 and 29.9 for syn uNHC and anti uNHC ligands, respectively, and thus within the same level of significance.…”
Section: Steric and Electronic Properties Of Unhcsmentioning
confidence: 99%